The Fight Against Panax notoginseng Root-Rot Disease Using Zingiberaceae Essential Oils as Potential Weapons - Yin, Yan-Jiao; Chen, Chuan-Jiao; Guo, Shi-Wei; Li, Ke-Ming; Ma, Yu-Nan; Sun, Wu-Mei; Xu, Fu-Rong; Cheng, Yong-Xian; Dong, Xian (Frontiers in Plant Science, 2018)
The root of Panax notoginseng is one of the most highly valuable medicinal herbs in China owing to its pronounced hemostatic and restorative properties. Despite this important fact, growing P. notoginseng is seriously limited by root-rot diseases. In studies aimed at developing a solution to problem, environment-friendly essential oils (EOs) of five medicinal plants of the family Zingiberaceae were tested for their inhibitory effects on the growth of three main soil pathogens associated with the root-rot diseases of P. notoginseng. The results showe that EOs of Alpinia katsumadai Hayata and Zingiber officinale Roscoe promote significant reductions in the mycelium growth of the pathogen in vitro at a concentration of 50 mg mL-1, which is much higher than that needed (5 mg mL-1) to reduce growth by the positive control, flutriafol. Furthermore, the chemical components of the two EOs were determined by using GC-MS analysis. Eucalyptol was found to account for more than 30% the oils of the two plants, with the second major components being geranyl acetate and α-terpineol. These substances display different degrees of fungistasis in vitro. To further determine the effects of the EO of Z. officinale in vivo, soilless cultivation of P. notoginseng with pathogen inoculation was conducted in a greenhouse. Addition of the petroleum ether extract (approximately equal to EO) of Z. officinale to the culture matrix causes a large decrease in both the occurrence and severity of the P. notoginseng root-rot disease. The decreasing trend of net photosynthetic rate (Pn), stomatal conductance (gs), intercellular CO2 concentration (Ci) and transpiration rate (Tr) were all alleviated. In addition, the activities of catalase (CAT), peroxidase (POD) and the malondialdehyde (MDA) content were also largely reduced after pathogen infection, with the root activity being higher than that of the control. Taken together, the findings reveal that EOs from plants might serve as promising sources of eco-friendly natural pesticides with less chemical resistance.